Calorimetric study of nanocomposites of multiwalled carbon nanotubes and isotactic polypropylene polymer. Issue 1 (20th March 2013) - Kalakonda, Parvathalu; Iannacchione, Germano S.; Daly, Michael; Georgiev, Georgi Y; Cabrera, Y.; Judith, R.; Cebe, Peggy
Abstract Modulated differential scanning calorimetry (MDSC) was used to measure the complex specific heat of the crystallization and melting transitions of nanocomposites of isotactic polypropylene (iPP) and carbon nanotubes (CNT) as function of CNT weight percent and temperature scan rate. In the last few years, great attention has been paid to the preparation of iPP/CNT nanocomposites due to their unique thermal and structural properties and potential applications. As the CNT content increases from 0 to 1 wt %, heterogeneous crystal nucleation scales with the CNT surface area. Above 1 wt %, nucleation appears to saturate with the crystallization temperature, reaching ∼8 K above that of the neat polymer. Heating scans reveal a complex, two‐step, melting process with a small specific heat peak, first observed ∼8 K below a much larger peak for the neat iPP. For iPP/CNT samples, these two features rapidly shift to higher temperatures with increasing ϕw and then plateau at ∼3 K above that in neat iPP for ϕw ≥ 1 wt %. Scan rates affect dramatically differently the neat iPP and its nanocomposites. Transition temperatures shift nonlinearly, while the total transition enthalpy diverges between cooling and heating cycles with decreasing scan rates. These results are interpreted as the CNTs acting as nucleation sites for iPP crystal formation, randomly pinning a crystal structure different than in the neat iPP and indicating complex transition dynamics. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013